Hubungan Usia Dan Paritas Ibu Dengan Kejadian Postpartum Blues Di PMB “W” Magetan - Oktavia Puspita Sari; Agung Suharto (Gema Bidan Indonesia, 2021)
Indonesia's postpartum blues incidence is 50-70% of postpartum women, postpartum blues occur in postpartum women caused by several factors such as childbirth experience, increased hormones, infant behavior, maternal age, and parity. The aim of the study was to determine the relationship of age and parity with the incidence of postpartum blues in PMB "W" Magetan. Type of analytic research, cross-sectional study design, the postpartum maternal population in Magetan PMB "W" 24 respondents, 23 respondents were taken by accidental techniques, free age, and parity variables while dependent variable postpartum blues. Data collection with EPDS questionnaire, data analysis using chi-square test. The results of the study obtained mothers with primipara 83%, and in multiparas 17%, mothers aged <20 years 44%, at the age of 20-35 years 26% and age> 35 years 30%. The results of statistical tests on age variables with the incidence of postpartum blues obtained p= 0.031 (0.05) so it was concluded that there was a relationship between age and postpartum blues events, the results of statistical tests on variable parity with postpartum blues events obtained p = 0.040 (0.05) so it can be concluded that there is a relationship between parity postpartum blues. The conclusion of the study is that there is a relationship between parity and age with postpartum blues events, it is suggested that prospective mothers can prepare the pregnancy properly so that it will minimize the incidence of postpartum blue, and midwives can detect symptoms of postpartum blues so that they can prevent postpartum blues.